Serum mineral status during pregnancy in cows - Yildiz, Hamit; Kaygusuglu, Erdal; Aydin, Muhterem (Indian Counc Agricultural Res, 2006)
In this study, the serum concentrations of calcium (Ca), zinc (Zn), copper (Cu), iron (Fe), potassium (K) and sodium (Na) in 12 cows, 3-8 year old,, during pregnancy and post-partum, and the relations among such parameters were researched. Parallel variations Of Serum Ca and Cu concentrations were noticed. They significantly increased from the fifth month, were maximal on the sixth month and thereafter they gradually declined until the parturition day Zn concentrations were found modified (from the third month) and remained elevated throughout the pregnancy, with maximal values on the fourth and fifth months. Fe, Na and K tended to decrease during pregnancy. From the third to the eighth month a significant decline of Fe was observed, and K concentration were particularly lower on the fifth and the seventh month. Na concentrations fluctuated, marked decrease of Na were observed on the Fourth month and on the ninth month and during postpartum. The important correlations were determined between Ca-Cu, Ca-Zn, Ca-Fe, Cu-Zn in various months of pregnancy and the day of delivery. A significant relation was found between Fe-Zn during the pregnancy. Any change due to the delivery status was not determined in the levels of Ca, Cu, Zn, Fe, K and Na during the pregnancy and postparturition. In Conclusion, it was agreed that the levels of serum Ca, Cu and Zn levels decreased as determined during the last months of the pregnancy and postparturition.
Keywords: cows; mineral status; pregnancy